Study of the pattern, intent behind and outcome of acute poisoning in a tertiary care centre - Srinivas, G.; Aashik, Y. S.; Muthalik, Manoj (International Journal of Advances in Medicine, 2020)
Background: Acute poisoning is one of the major medical emergencies with significant morbidity and mortality. Appropriate planning, prevention and management techniques can be designed by knowing the nature, severity and outcome of acute poisoning cases. Most of the poisoning is due to the intention of deliberate self-harm. This study aimed to study the pattern and outcome of acute poisoning and the intent behind poisoning. Methods: This is a cross sectional study which included 100 acute poisoning cases in a tertiary care hospital. The study includes data regarding age, sex, time elapsed after intake of poison; name of the poisonous substance, duration of hospitalization, severity and outcome were collected in the prestructured proforma. Intent behind poisoning was calculated using Beck’s suicide intent score. Results: Incidence was more common among males (69%) but there was no significant correlation between gender and mortality. Mean age of presentation was 35.66 years but age of presentation and mortality correlation was not statistically significant (t=0.92, p=0.3). Organophosphorous compound poisoning (36%) was the most common type of poisoning. Total mortality was found to be 12%. Beck’s suicide intent scores were higher in patients who died and statistically significant (t=8.96, p=0.0001). Maximum patients expired when there was a delay in admission to hospital by more than 8 hours after exposure. Conclusions: Poisoning is more common in young males. The overall mortality depends on type of poison, time elapsed since exposure to hospital arrival, suicidal intent and many other factors. Early care in a tertiary care center may help to reduce mortality in India.